The Burden of Diseases and Injury through The Lens of Standard Expected Years of Life Lost: The Lost Productivity and The Distribution of Health Attainment in Countries of Different Health Systems - Eduardo Daniel López-Vila; Pavitra Paul (Epidemiology, Biostatistics and Public Health)
Background: The productivity loss attributable to the burden of diseases in different country contexts reflect the effectiveness of the context specific measures for population health development. So, this study provides insights into the productivity loss from the burden of diseases.